Crop-livestock interactions and implications for animal traction research in the Ethiopian highlands - Asamenew, G.; Zerbini, E.; Tedla, A. (Institute of Agricultural Research, 1993)
Crop and livestock subsystems in the Ethiopian highlands interact with each other in many wasy. The livestock subsystem has output, input, asset, and security and investment functions in the farming system. Animal traction and crop residues are the prominent binding elements of the crop and livestock subsectors. Expansion of cultivated area, better cropping pattern, labour savings, and contribution to increased yields are the important effects of animal traction on the crop subsector. There is a potential for the lviestock and the crop subsystems to further contribute to each other. Research areas to exploit this potential are suggested. Some constraints to technology transfer are also highlighted.